Ovum pickup at different times of a synchronized follicular wave did not affect IVP in Bos indicus, Bos taurus, or Bubalus bubalis - Gimenes, Lindsay Unno; Ferraz, Márcio Leão; Araújo, Anderson; Fantinato Neto, Paulo; Chiarati, Marcos Roberto; Mesquita, Lígia Garcia; Arango, J. S. P.; Raposo, M.; Souza, Diego Cavalcante de; Calomeni, Gustavo Delfino; Gardinal, Rodrigo; Villanueva Rodriguez, Cindy Libeth; et al. (CSIRO Publishing, 2010)
One important factor in the success of ovum pickup (OPU)/IVP in Bos taurus is the follicular status at OPU concerning the dominance period (Hendriksen et al. 2000 Theriogenology 53, 11-20). The hypothesis of the present study is that OPU performed after follicle deviation, when follicles show a mild level of atresia, improves competence for IVP in Nelore (NE), Holstein (HO), and buffaloes (BU). Objectives were to determine effects of OPU done at different times of synchronized follicular wave (1, 3, or 5 d after expected emergence) and of genetic group (NE, HO, and BU) on IVP. A total of 27 heifers (9 of each genetic group) were maintained in contemporary nutritional and environmental conditions during experiment, in a cross-over design, performed in 6 replicates. Recovered oocytes with at least one cumulus cell layer were matured in TCM-199 supplemented with 10% of FCS plus 50 μM of cysteamin and 0.3 mM of cystine, at 38.5°C with 5% CO2 in air for 24 h. IVF was done with 2 × 106 spermatozoa per mL of NE (for bovine oocytes) or BU semen (for BU oocytes), for 20 h at the same incubator conditions of IVM. After IVF, presumptive zygotes were denuded and cultured in SOF under the same previous atmosphere conditions. Medium was changed 3 d after IVF when cleavage rate (CR) was assessed. Blastocyst (BR) and hatching rates (HR) were evaluated 7 and 9 days after IVF, respectively. About 50% of hatched blastocysts were fixed until nuclei counting. Data were analyzed by ANOVA using the Proc Mixed model. No effects of interaction or time of synchronization were observed in any of the variables. Concerning genetic group, NE had better results than HO and BU (mean ± SEM / heifer / replicate), respectively, for visualized follicles (41.0a ± 2.1, 22.1b ± 1.3, 18.8b ± 0.9), total oocytes (37.1a ± 2.5, 15.4b ± 1.2, 14.8b ± 1.0), oocytes at IVM (30.8a ± 2.4, 10.7b ± 1.0, 7.9b ± 0.7), oocytes at IVC (18.7a ± 0.8, 8.0b ± 0.5, 7.5b ± 0.4), cleaved embryos (15.4a ± 0.7, 4.6b ± 0.4, 4.4b ± 0.3),CR(81.8a, 59.1b, 62.3b), blastocysts on Day 7 (5.1a ± 0.6, 1.0b ± 0.2, 0.6b ± 0.1), BR (25.8a, 13.6b, 9.1b), and hatched blastocysts on Day 9 (2.6a ± 0.4, 0.3b ± 0.1, 0.3b ± 0.1). Recovery rate and HR were greater for NE (89.4 and 50.6%, respectively) than for HO (73.3 and 23.2%), but neither differed from BU (82.8 and 31.9%). Also, the percentage of viable was greater for NE (83.0) than for HO (66.9) and BU (53.1). No effects were observed for nuclei counting (NE = 176.6 ± 5.3, HO = 168.9 ± 13.7 and BU = 206.1 ± 23.1). Results demonstrate that Nelore had a better efficiency for IVP than Holstein and buffaloes. OPU performed at different times of synchronized follicular wave did not influence IVP, conversely to the initial hypothesis of this study.